Hibernation changes tissue specific lipophilic profile of Chilo partellus (Swinhoe) - Sau, Ashok K.; Dhillon, Mukesh K.; Kumar, Sandeep; Tanwar, Aditya K. (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Lipids and cholesterol were higher in pre-hibernation, declined during hibernation.•Lipids and UFAs were highest in larval fat body than haemolymph and integument.•Lipophilic compounds other than fatty acids were higher in larval haemolymph.•UFAs were lower in haemolymph, fat body of post-hibernation pupae than counterpart. Chilo partellus undergo hibernation to survive under harsh winter conditions. We investigated changes in lipophilic profiles of larval and pupal whole body and tissues (haemolymph, fat bodies and integument) of hibernation and non-hibernation C. partellus strains. Significantly higher amount of lipids was found in whole body of pre-hibernation and hibernation larvae than non-hibernation larvae. At tissue level, total lipids were significantly higher in haemolymph and fat bodies of pre-hibernation, and integument of non-hibernation larvae. In whole body of larvae and pupae of hibernation and non-hibernation strains, most abundant fatty acids were oleic acid (16.4%–23%), palmitic acid (14.6%–19.3%), linoleic acid (9.3%–11.6%), palmitoleic acid (3.7%–7.3%) and stearic acid (1.7%–2.8%). Further, at tissue level, myristic, palmitoleic, palmitic, linoleic and oleic acids in fat bodies; and stearic acid in the integument of hibernation larvae were higher as compared to other body parts and larval stages of C. partellus. In pupal tissues, myristic, palmitic and stearic acids were higher in the haemolymph and fat bodies of non-hibernation pupae than post-hibernation pupae. Among the unsaturated fatty acids (UFAs), the palmitoleic acid significantly increased in all the larval tissues, and linoleic acid in fat bodies and integument, while oleic acid significantly decreased in integument of hibernation as compared to non-hibernation larvae of C. partellus. These information on adaptive remodelling of lipids at tissue level might help in future physiological, molecular, ecological and pest management studies on C. partellus.